Algorithm for Assessment of Students' Individual Choice of Sports Sections - Ж. О. Цимбалюк; Л. В. Коник; В. А. Тихонова (OVS LLC, 2016)
Research objective. To develop a model of students' decision-making when individually choosing a sports section. Research methods: The study relies on the analysis of scientific and methodological literature, questionnaires, and factor analysis. The participants in the study were 55 first-year students (2015 enrollment year) of the School of Ukrainian Language and Literature of H.S. Skovoroda Kharkiv National Pedagogical University. Research results. The analysis of the questionnaires showed diverse motivational choices. The factor analysis revealed the prevailing motifs. The study comes up with a hierarchical model of students' choice of a training section by a particular sport, and determines the system of subjective values of each student in points. Conclusions. The model developed by the hierarchy analysis allows to take into account all the variants of priorities in the students' motivational choice. The method of hierarchy analysis allows to objectively process the subjective advantages seen by the students (who do not have any sports experience) when choosing a training section in the opted-for sport. This, in its turn, cultivates a steady motivation for physical education, allows to determine the required number of sports sections, and to distribute the educational and sports facilities at the higher educational university.